The Perceived Role of Non-Elected Actors in Community Power Structure in Poland: Results of a Survey Experiment - Pawel Swianiewicz (Transylvanian Review of Administrative Sciences, 2024)
Administrative decisions can be influenced not only by policies formulated by elected representatives but also by various external actors. From classic elitist and pluralist theories of community power to urban regime and network governance concepts, academic studies tell us that several institutional and individual actors with no electoral democratic legitimacy may have a significant impact on local government decision-making. In our paper, we ask the question who they are in contemporary Polish cities. Are there any systematic regularities in this respect concerning e.g. how they differ depending on the size of the local community? In this paper we look at the phenomenon through the lens of citizens’ perception of the influence on important administrative decisions made in local governments. In this research, we also check whether the style of local political leadership perceived by citizens is reflected in their expectations toward the propensity of local authorities to consider the opinions. Data is collected through a survey conducted on a representative sample of 2,000 Polish citizens who were asked about their perception of the impact of various business and societal actors. The study uses the survey experiment method in which various formulations of the question are randomly assigned to individual respondents, which allows us to measure the perceived influence of individual types of actors. Referring to the recent debate on the limitation of the applicability of regime theory to large cities only, we place a special attention to the impact of city size on the role of big and small businesses as well as various societal organizations.